Migration and Remittances, April 2017 : Recent Developments and Outlook - World Bank Group (World Bank, Washington, DC, 2018)
This Migration and Development Brief provides an update on worldwide remittance flows and the global migration crisis. It focuses on two Sustainable Development Goal (SDG) indicators: reducing remittance costs, and reducing recruitment costs for low-skilled migrants. In September 2016, the United Nations General Assembly Summit on “Large Movements of Refugees and Migrants” committed to develop two global compacts: a Global Compact on Refugees, and a Global Compact for Safe, Orderly, and Regular Migration. Negotiations on both compacts are expected to continue through 2017, with final adoption expected at a United Nations international conference in 2018. The Brief reports on progress in the preparation of the global compacts, with an expanded discussion of the Global Compact on Migration.